KECERDASAN EMOSIONAL SEBAGAI PREDIKTOR PRESTASI BELAJAR SISWA SMA: KAJIAN SISTEMATIS TERHADAP DIMENSI PENGATURAN DAN MOTIVASI DIRI - Basir Jarah Anilon; Ahmad T. Zainal Abidin; Syafii, Hisyam; Halim Purnomo; Azhari, Husain (IAI Sunan Giri Trenggalek, 2026)
This study aims to examine the influence of emotional intelligence on the academic achievement of public high school students through a systematic literature review approach. Emotional intelligence is defined as an individual's ability to recognize, understand, manage, and express emotions adaptively, which includes five main dimensions: self-awareness, self-regulation, self-motivation, empathy, and social skills. This study uses a systematic literature review method guided by PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). A literature search was conducted through the Google Scholar, Sinta, and DOAJ databases using the keywords